Challenges of Online Learning Faced by Efl Students During Covid 19 Pandemic - Ulfa, Kurnia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Covid-19 pandemic brings changes in many aspects of peoples’ lives throughout the world. The spread of Covid-19 in Indonesia affects the education system in this country. Face-to-face instructions are shifted into full online learnings from home. The findings disclosed that these EFL students’ main challenges in attending online learning were the unsteady networks and the less direct interactions. These students mainly suggested the use of video conferencing applications such as zoom or Google meet, though some students chose assignments over those applications. The students also mentioned that they basically needed grammar related materials within the online classes. The findings bring forward the picture of full online learning condition during Covid-19 outbreak on EFL setting in Indonesia